Public Relations, Biopolitics, & Aestheticization: The Instrumenting of Identity in Relation to Sociopolitical Conflict - Walker, Hailey (Université Saint-Paul / Saint Paul University, 2019)
Contemporary experiences and conceptions of sociopolitical conflict in the West are dominated by the notion of representative identity politics. However, how do Western perceptions of identity itself – particularly, against a cultural backdrop of consumer individualism – contribute toward this domination? Namely, in what ways does the Western perception and experience of identity result in the increasingly prevalent tendency of institutions and civic masses to position themselves in sociopolitical conflict via direct identity appeals and demands? This research aims to explore the ways in which the combined and constitutive effects of the public relations industry and the vast network of biopolitics (namely, continual processes of instrumentalizinging identity) results in an aestheticized politics of identity that sees sociopolitical antagonism experienced and measured solely in spectral terms. Further, this research aims to identify the ways in which this ‘spectral materialism’ hinders constructive political thought and action in relation to sociopolitical conflict.
Keywords: Biopolitics; Public Relations; Aestheticization; Spectral Materialism; Identity; Edward Bernays; Michel Foucault; Walter Benjamin; Sociopolitical conflict; Identity politics